The Effect of Erythromycin in Macrolide-resistant Bordetella pertussis: Inhibitory Effect on Growth, Toxin Expression, and Virulence - Jiang, Kaichong; Luan, Yang; Wang, Wei; Xue, Da; Tang, Shuyue; Peng, Xiaokang; Liu, Xiaoguai; Wang, Zengguo (Current Pharmaceutical Biotechnology, 2025)
IntroductionThe macrolide-resistant Bordetella pertussis (MRBp) has appeared in Asia and has even been prevalent in China. Since the antibiotic sensitivity test is not carried out in the clinical setting, macrolide is still the first choice of antibiotic in MRBp infection. Further, the macrolide therapy for pertussis needs to be revised. Macrolide has always shown a positive effect on other macrolide-resistant bacterium infections in clinical applications. However, the mechanism of macrolide on MRBp remains unclear.ObjectiveThe objective of this study was to investigate the effect of virulence of MRBp under the sub-MIC erythromycin.MethodsThis study evaluated a representative isolate BP19147 (ptxP1/fhaB3-MRBp) under a series of sub-inhibitory concentrations of erythromycin. We measured the growth curve, biofilm formation, and autoaggregation assay under Stainer and Scholte (SS) broth. The relative gene expression was detected by RT-qPCR.ResultsThe proteomics was detected by label-fee DIA. The growth ability and virulence factors of MR isolate BP19147 were inhibited by sub-MIC of erythromycin and had a concentration-dependent effect. From the proteomics results, the pertussis toxin, filamentous haemagglutinin, and pertactin did not show a statistical difference (p >0.05). Other virulence factors (including dermonecrotic toxin, Invasive Adenylate cyclase/haemolysin. etc) showed a statistical difference (p <0.05). In the KEGG enrichment, the BvgAS system, biofilm formation, and some adaptive systems were inhibited by erythromycin.ConclusionThe sub-MIC of erythromycin may reduce the virulence of MRBp, which will provide a theoretical basis for the rational use of erythromycin for MRBp infection and help the development of new antibiotics.
Keywords: erythromycin